The discovery of an asymmetric detached shell around the "fresh" carbon AGB star TX Psc. Issue Volume 14:Issue S343(2019) (August 2018) - Brunner, M.; Mečina, M.; Maercker, M.; Dorfi, E. A.; Kerschbaum, F.; Olofsson, H.; Rau, G.
Abstract: We present ALMA observations of the circumstellar envelope around the AGB carbon star TX Psc in molecular CO(2–1) emission, and detect a previously unknown detached shell with filamentary structure and elliptical shape. Up to now, all observed detached shells are found around carbon AGB stars and are of remarkable spherical symmetry. The elliptical shell around TX Psc is the first clear exception to that rule, with TX Psc being classified as rather ''fresh'' carbon star, that most likely has only experienced very few thermal pulses yet. We investigate and discuss the 3D structure of the CSE and its most likely formation scenarios, as well as the link of this peculiar detached shell to the AGB evolutionary status of TX Psc.